Architectural Ceramics of Ancient Samarkand - Khasanova Khafiza Bakhriddinovna; Imamov Mukhiddin Rustamovich (Research Parks Publishing LLC, 2021)
The article provides information about the types, applications and manufacture of tile ornaments i.e. architectural ceramics in the architectural monuments of ancient Samarkand, which attracted the attention of the world.